HUBUNGAN PERSONAL HYGIENE PERINEAL PADA PASANGAN USIA SUBUR TERHADAP KEJADIAN KEPTUHAN DI WILAYAH KERJA PUSKESMAS KEBUMEN I KABUPATEN KEBUMEN - Nurfitriyana Hidayati Hidayati; herniyatun -; suhartini - (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2010)
The problem that arises in every fertile age woman is leucorrhoea. It is a liquid that discharges from the vagina but it is not blood. Leucorrhoea can be started from the bad genetalia care that this can make the area not moisture. If the genetalia area is in moist and dry conditions , it will lead germs, bacteria and fungi to grow and the condition can cause leucorrhoea. This study aimed to find out correlation between perineal personal hygiene of the fertile women with leucorrhoea occurrence in the work area of Kebumen 1 Community Health Center. This was a descriptive correlation research that used cross sectional approach. The total populations were 298 and the samples taken were 75 respondents. The researcher used simple random sampling technique to obtain the samples. Chi square analysis test was used to find out correlation between perineal personal hygiene of the fertile women with leucorrhoea occurrence. The findings showed that in perineal personal hygiene variable; there were 58 respondents (77.3%) had less category and 6 respondents (8%) had good category of , of the less criteria are while both criteria were). Meanwhile in the leucorrhoea occurrence; there were 56 respondents (74.7%) experienced leucorrhoea physiologically and 19 respondents (25.3%) experienced leucorrhoea pathologically. There is a correlation between perineal personal hygiene of the fertile women with leucorrhoea occurrence (p ≤ 0.024 <0.05). Keywords : Perineal Personal Hygiene, Fertile Women, Leucorrhoea